New and Future Developments in Microbial Biotechnology and Bioengineering Microbial Genes Biochemistry and Applications - Singh, H. B.; Gupta, Vijai Kumar; Jogaiah, Sudisha (Elsevier, 2019)
New and Future Developments in Microbial Biotechnology and Bioengineering: Microbial Genes Biochemistry and Applications consolidates the most widely used genetic methods available, bringing together the fields of biochemistry, biotechnology and microbiology. Chapters give clear-and-concise direction on both standard and applied microbial genetic improvements, presenting undergraduates, post-graduates and researchers with the latest developments in microbial gene technology. In addition, the book describes the background and usefulness of each experiment in question. All chapters covered in the book are derived from current, peer reviewed literature accepted by the international scientific community